Physalis minima L. Fruit- A Promising Approach To Alzheimer's Disease - Litty Joseph; Chinchu Ravi (Elsevier, 2022)
Physalis minima L. belong to the family of Solanaceae has been traditionally used to prevent neurodegenerative disorders. The scientific values of the traditional claim haven't been explored yet. The present study aims to investigate the role of ethanol extract of Physalis minima L. fruit in learning, memory, and neurodegeneration in D- galactose induced Alzheimer' s model.The total phenolic and flavonoid content of the ethanol extracts of P. minima fruit was executed by Folin Ciocalteu and aluminium chloride colorimetric method respectively. It was further evaluated for nitric oxide scavenging assay and acetylcholinesterase inhibitory activity. The in vivo studies were performed by D- galactose induced Alzheimer' s model and the behavioural observations were executed using Y maze, Morris water maze, Elevated plus maze, Radial arm maze, and open field apparatus. Data were analysed by two-way ANOVA followed by Tukey' s multiple comparison test.The phytochemical analysis of the extract explored the presence of carbohydrates, glycosides, phenolics, flavonoids, proteins, terpenoids, steroids. The present study revealed the presence of 0.96 and 0.974 milli equivalence of flavonoids and phenolics. In vitro studies confirmed the role of antioxidant and acetylcholinesterase enzyme. The in vivo study revealed the reduced transfer latency, high corrected score in spontaneous alteration, low working and reference memory error, reduced escape latency, and normal locomotory activity. The histopathological analysis further confirmed the neuroprotective effect. The neuroprotective effect of P. minima L. provides new insight into the possible therapeutic use for treating Alzheimer' s disease and acetylcholinesterase inhibition may be a probable mechanism.